The Effect of The Characteristics of The Company On The Disclosure Of Corporate Social Responsibility (Empirical Studies On The Coal Industry Listed in Indonesia Stock Exchange in 2011-2013) - Indrayenti INDRAYENTI; . Velycia (Universitas Bandar Lampung (UBL), 2015)
This study aims to identify and analyze the effect of profitability, leverage, firm size, and sizeof board of commisioner on the disclosure of social responsibility in the Coal industry that listed in Indonesia Stock Exchange period 2011-2013. The first hypothesis is profitability has positive effect on Corporate Social Responsibility (CSR) disclosure, the second hypothesis is leverage has negative effect on Corporate Social Responsibility (CSR) disclosure, the third hypothesis is size firm has positive effect on Corporate Social Responsibility (CSR) disclosure, the fourth hypothesissize of board of commisioner is has positive effect on Corporate Social Responsibility (CSR) disclosure.Measurement of corporate social responsibility is based on the category of the Global Reporting Index (GRI) G3 Guideliness is seen in the company's annual financial statements. The sample in this study is coal industry that listed in Indonesia Stock Exchange 2011-2013. Sampling technique used in this study is purposive sampling, so that obtained 15 companies.Profitability measured by Return on Assets (ROA), leverage is measured using a Debt Equity Ratio (DER), Company size is measured by total assets, and size of board of commisioner is measured by amount ofcommissionersinthe company. The technique of data analysis done with the classical assumption, hypothesis testing using multiple linear regression analysis using SPSS 18.0 for windows. The results showed that in partial profitability, firm size, and size of board of commisioner has positive influence on CorporateSocial Responsibility (CSR) disclosure in the coal industry are listed in the Indonesia Stock Exchange, while the variable leverage negatively affects Corporate Social Responsibility (CSR) disclosure inthe coal industry are listed in the Indonesia Stock Exchange.